KAJI EKSPERIMENTAL PENGGUNAAN KOMPOSIT KAMPAS REM SERAT IJUK PADA SEPEDA MOTOR YAMAHA JUPITER Z - Ferindra Alim; Ranto Ranto; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The aims of this study are: (1) To test the value of Hardness composite brake lining palm fibers (2) To test the wear rate of the brake lining from palm fibers (3) To estimate the using period of the brake lining from palm fibers. This study used an experimental method. The analysis technique in this study was used descriptive analysis. The wear rate of palm fibers brake pads was tested by using road test. Sample of this research taken by purposive sampling method. The sample of this research is composite palm fibers brake pads with 55% palm fibers, brass powder (Cu-Zn) 15%, magnesium oxide (MgO) 20%, and 10% epoxy resin. Comparison of composite material was mixtured by using comparison of mass. The result of this study are: (1) The value of hardness the composite brake lining from palm fibers approached the brake lining that are on the market, where the Brinell Hardness test results of composite brake lining from palm fibers 10.07 BHN and brake lining Indoparts 12.67 so composite brake lining palm fibers can be applied on a motorcycle, (2) The wear rate of the brake lining palm reached 0.000314 mm/km, (3) The test results showed that the using period of composite brake lining palm fiber that have a thickness of 5 mm can be used reach 14 331 km or 107 484 times braking, this proves that the brake lining of palm fiber is recommend to produce.